Encountering Paul : understanding the man and his message - Wiley, Tatha (Come & see., 2010)
Fascinating, controversial, yet enigmatic, the figure of the apostle Paul looms large in Christian history. But which Paul is the true one? Is it the Paul who proclaims our freedom in Christ or the Paul who demands that slaves obey their masters? The Paul who works closely with women evangelists, or the Paul who instructs women to submit to the rule of their husbands? Is it the deeply Jewish Paul or the Paul who rejects the Law? Drawing on the literary and historical insights that have revolutionized contemporary Paul scholarship, Tatha Wiley skillfully separates these different voices of Paul and their liberating and oppressive legacies. In her well-crafted work, Wiley not only illumines the authentic, historical Paul but also accounts for the misapplication of his teachings in the history of slavery, male domination, religious exclusivism, and anti-Judaism.